(untitled) (Fiep Bulletin - online, 2011)
The present study it had as objective to verify the effect of the Bilateral Transference of Learning in the handling of Lien Tien Chuan of Kung Fu style Praise-the-God seven stars. The Bilateral Transference of Aprendizagem (TBA) if of when a learned ability is transferred to the contralateral member. Lien Tien Chuan one is about a weapon articulated used old in combats for the orientals to attack in vital points, to apply keys in the joints and strangulations, but with the disadvantage of the instability of the weapon due its joint. For such research, we count on 10 citizens of the masculine sex with age enters 20 - 30 years physically active that had been divided in two groups of five people each. The groups had been nominated as practical group of with member not preferred (NP) and group for practical with the preferred member (p). The tests had been carried through in the laboratory of research of a University of Barueri/SP and in a Club of the City hall of SÃ£o Paulo and each citizen of the group an only time for practical had right of 10 tests for the learning of the manuscript having with the contralateral member that was after the ten tests. After this, three observers had analyzed together the videos with performance of each citizen transcribing the data for a spread sheet where the results had pointed one better TBA with respect to group NP of what of group P.